2016
DOI: 10.13189/ujar.2016.040404
|View full text |Cite
|
Sign up to set email alerts
|

Effective Selection Criteria for Screening Drought Tolerant and High Yielding Bread Wheat Genotypes

Abstract: Bread wheat is the major staple food in Morocco. Drought is the most important abiotic stress decreasing yield. Breeding for drought tolerance may be improved by various plant traits. In order to investigate the best selection criteria to develop drought tolerant varieties, 40 bread wheat genotypes were evaluated under two locations representing the stressed and non-stressed environments, using randomized complete block design with three replications during the cropping season 2014. Under stressed conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…(2018) in which they reported that DSI and STI indices were most useful to identify genotypes differing in their response to drought. The high GY under WD and WW conditions, in some genotypes, supported by the results of other researchers (Bennani et al., 2016; Kandic et al., 2009; Mujtaba et al., 2018) in which they reported that some of the genotypes that performed well under optimum conditions (WW) also performed well under WD.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…(2018) in which they reported that DSI and STI indices were most useful to identify genotypes differing in their response to drought. The high GY under WD and WW conditions, in some genotypes, supported by the results of other researchers (Bennani et al., 2016; Kandic et al., 2009; Mujtaba et al., 2018) in which they reported that some of the genotypes that performed well under optimum conditions (WW) also performed well under WD.…”
Section: Discussionsupporting
confidence: 77%
“…For example, late flowering and taller genotypes tend to produce higher GY under WW conditions; in contrast, under WD conditions, earlier and shorter wheat genotypes tend to produce higher GY. The previous results indicated that some genotypes can partially avoid drought stress at the most critical growth stages by flowering earlier (Bennani et al., 2016; Kandic et al., 2009; Sharma et al., 2008). Therefore, growing dwarf and semi‐dwarf wheat cultivars under drought conditions could result in extremely short plants that might not be suitable for machine harvesting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For drought tolerance that could be drought tolerance per se (direct selection) or a related trait(s) (indirect selection) that is more heritable or easier to identify. Generally, breeding for improved drought tolerance in cereals must be combined with good yield potential [98] because there are occasional seasons with above-average moisture. From these crosses, plant breeders select elite progeny for drought tolerance.…”
Section: Advances In Breeding For Drought Tolerancementioning
confidence: 99%
“…Grain weight Sharma et al (2008); Sareen et al (2012), Bennani et al (2016) b. Grain filling rate and duration Nawaz et al (2013), Khan and Kabir (2014), Song et al (2015) c. Number of fertile spikes Khan and Kabir (2014), Bennani et al (2016) 3.2.1 Conserving soil moisture A continuous supply of water is necessary for sustaining the grain-filling rate and duration, and grain size in wheat. This could not be possible in rain-fed wheat growing area, but here, mulching can be the best option for maintaining optimum moisture and thermal regimes in the soil system.…”
Section: Agronomic Managementmentioning
confidence: 99%